PagHAM4a-PagSCL21 and PagHAM4b-PagTCP20 modules positively regulate cambial activity and its differentiation into secondary xylem in poplar - Zhao, Pan (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.